(untitled) (Research, Society and Development, 2021)
Dogs are definitive hosts of some diseases caused by parasites, which sometimes the owners do not even know about the need for deworming. Soil contamination by dog ​​feces in public squares has been the subject of several researches, in order to reveal the importance of these places as favorable areas for the transmission of parasites. The objective of this work was to evaluate the occurrence of zoonotic parasites in dog feces using the Willis-Mollay technique, from public squares in different areas of the city of Porto Velho - Rondônia, Brazil, namely the South Zone, North Zone, East Zone , West Zone and another in the Central region. A total of 10 feces were collected as a sampling of each region mentioned above, which were later processed and the results obtained through the Willis-Molay technique were investigated. As a final product of checked samples (50), 75% proved to be positive for Ancylostoma sp. and 25% for Toxocara sp. The squares in the East and South Zones were the ones with the largest amount of contaminated samples. The association of the parasites Ancylostoma spp. and Toxocara sp. in the same sample, seen in all squares, being more frequent (20%) in the East Zone square.